Is low-nicotine Marlboro snus really snus? - Furberg Helena; Foulds Jonathan (Harm Reduction Journal, 2008)
Abstract Swedish snus is a medium/high nicotine delivery, low-nitrosamine moist smokeless tobacco product that has been estimated to be at least 90% less harmful than smoked tobacco. More men use snus than smoke cigarettes in Sweden, and a quarter of male former smokers quit by switching to snus. Leading multinational cigarette manufacturers have begun test-marketing snus-like products in the United States and other countries. The version of Philip Morris' Marlboro snus currently being marketed in the United States differs from Swedish snus in many ways; it has lower moisture content and pH, but most puzzling is its very low nicotine delivery. Philip Morris, the market-leader in United States cigarette sales, may have designed the product so that it does not satisfy nicotine cravings and fails to enable smokers to switch. In this paper we compare and contrast Swedish snus and Marlboro snus, and speculate as to why Philip Morris may have intentionally designed a product that delivers very low levels of nicotine. We recommend that Philip Morris cease using the term "snus" to refer to dry tobacco products with low nicotine delivery, so that the term be reserved for moist, low-toxin, medium/high nicotine delivery smokeless tobacco products that are qualitatively similar to the leading brands in Sweden.